MATH IS FUN: Bachelor of Science in Business Administration - Garry Alfonsius (Universal Journal, 2021)
In this paper will tell you math is fun. More people think that math really hard but math will be fun if we want to know more. For me math makes me want to push my limit so I always want to know more and more about it. This paper will tell you about historical math for the first spot and the second will be as usual like the general of math like variable, and geometry. The study of math within early civilizations was the building blocks for the math of the Greeks, who developed the model of abstract mathematics through geometry. Greece, with its incredible architecture and complex system of government, was the model of mathematic achievement until modern times.